Driving Consumer Adoption in Private Household Waste Collection Services: Insights from Indonesia - Nadiya Rahmawati; Nila Armelia Windasari (Publikasi Indonesia, 2025)
Waste management that is not managed properly can have various negative impacts on ecosystems and the environment, especially the health of living things. One solution is through household waste collection services. However, there are behavioral challenges that must be overcome to achieve optimal waste management practices. This study aims to investigate the factors that affect people's intention to use household waste collection services in Indonesia. The research method used is an online survey with convenience sampling techniques, with a sample of 200 respondents. Data analysis uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to test validity, reliability, and relationships between variables. The results of the study show that environmental awareness, social norms, ease of use, and perceived value significantly affect people's intention to use household waste collection services. These findings provide valuable insights for service providers and policymakers to develop more effective strategies in driving the adoption of household waste collection services in Indonesia. The practical and theoretical implications of this study are discussed in detail